Counseling on Clean and Healthy Living Behavior in Early Childhood in Belimbing Village, Tangerang Regency - Heriyanti; Ummanah; Safiani A. Faaroek; Ayu Larasati; Amadea Yohana; Hakim Rizki Alfaza; Luki Kristina; Octaviani Anggraenita; Veby Husada; Widiyaningsih (PT FORMOSA CENDEKIA GLOBAL, 2023)
From the results of the location survey, there are still many residents of Belimbing Village who throw garbage in any place. To anticipate this, counseling activities were carried out regarding the importance of clean and healthy living behavior (PHBS). Counseling activities carried out using lecture methods, demonstrations and question and answer. PHBS counseling participants are early childhood who are residents of Belimbing Village with ages between 4-7 years. The stages in the implementation consist of the preparation, implementation and evaluation stages. The participants in the extension activities were very enthusiastic about participating in the extension activities. The results obtained from this counseling activity are children as participants being able to understand, know and demonstrate the importance of clean and healthy living behavior in the family and community environment.